Mechanism of nascent chain removal by the ribosome-associated quality control complex - Wenyan Li; Talia Scheel; Peter S. Shen (Nature Communications)
Abstract Errors during translation can cause ribosome stalling, leaving incomplete nascent chains attached to large ribosomal subunits. Cells rely on the Ribosome-associated Quality Control (RQC) complex to recognize, process, and remove these aberrant proteins to maintain proteostasis. Despite its importance, the mechanisms by which the RQC orchestrates nascent chain processing and extraction have remained unclear. Here, we present a cryo-EM structure of the RQC complex from budding yeast, revealing how its core components function in nascent chain removal. We show that the Cdc48 ATPase and its Ufd1-Npl4 adaptor are recruited by the Ltn1 E3 ubiquitin ligase to extract ubiquitylated peptides from the 60S ribosome. Additionally, we find that Rqc1 bridges the 60S subunit with ubiquitin and Ltn1, facilitating formation of K48-linked polyubiquitin chains. These findings provide a structural and mechanistic framework for understanding how the RQC complex collaborates to clear stalled translation products, advancing insight into cellular protein quality control.